Intricate ethics: rights, responsibilities, and permissible harm - Kamm, F. M. (Oxford ethics series, 2007)
Nonconsequentialism -- Aggregation and two moral methods -- Intention, harm, and the possibility of a unified theory -- The doctrines of double and triple effect and why a rational agent need not intend the means to his end -- Toward the essence of nonconsequentialist constraints on harming : modality, productive purity, and the greater good working itself out -- Harming people in Peter Unger's Living high and letting die -- Moral status -- Rights beyond interests -- Conflicts of rights : a typology -- Responsibility and collaboration -- Does distance matter morally to the duty to rescue? -- The new problem of distance in morality -- Peter Singer's ethical theory -- Moral intuitions, cognitive psychology, and the harming/not-aiding distinction -- Harms, losses, and evils in Gert's moral theory -- Owing, justifying, and rejecting